O empreendedorismo na ficção de José Clemente Pozenato : mito e expressão de regionalidade - Tonet, Charles (My University, 2018)
The following thesis is about the mystification process of entrepreneurship as a regionality expression of the Italian Colonial Region (ICR), which has as discursive sources: historians, public authorities, class entities and entrepreneurs. Based on the analysis of the regional economic historiography and on its major business symbol, Abramo Eberle, the purpose is to identify the connections between this historical narrative and the fictional one in the Gardone family’s entrepreneurial trail, present in the immigration trilogy: A Cocanha, O Quatrilho and A Babilônia, by José Clemente Pozenato. Therefore, this project aims to discuss the entrepreneurship as a regionality manifestation, which examines the mythical speech based on Mircea Eliade’s concepts and to identify how the characters’ logic and its range of moral values represent the traditional principals of the entrepreneurial model.
Esta dissertação trata do processo de mistificação do empreendedorismo como expressão de regionalidade da Região Colonial Italiana (RCI), que tem como agentes discursivos historiadores, poder público, entidades de classe e empresários. A partir da análise da historiografia econômica regional e da biografia do seu maior símbolo empresarial, Abramo Eberle, objetiva-se identificar as relações entre essa narrativa histórica e a ficcional na trajetória empreendedora da família Gardone, presente na trilogia da imigração A Cocanha, O Quatrilho e A Babilônia, de José Clemente Pozenato. Dessa forma, este estudo procura discutir o empreendedorismo como manifestação de regionalidade, a qual passa pelo discurso mítico fundamentado nos conceitos de Mircea Eliade, e identificar como a lógica dos personagens e sua teia de valores morais representam os princípios tradicionais do modelo empreededor.
Keywords: Empreendedorismo; Migração; Economia regional - Itália - História; Pozenato, José Clemente, 1938 -; Entrepreneurship; Emigration and immigration; Regional economy - Italy - History